2018
DOI: 10.1159/000487132
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Ocular Myasthenia Gravis in an Argentinian Population

Abstract: Background: We investigated the prognosis of patients with myasthenia gravis (MG) initially presenting with only ocular symptoms in an Argentinian population. Summary: We performed a retrospective analysis of 61 patients with MG with pure ocular involvement at onset. Generalized MG (gMG) developed in 73.7% of patients, while the rest only exhibited ocular symptoms throughout the course of the disease (ocular MG [oMG]). The AChR antibody (AChR-ab) was found in 81.4% of the gMG and 50% of the oMG cases. AChR-ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…Seropositivity for AChR-Ab as a predictor of generalization is well-documented [ 5 , 7 , 9 11 , 13 , 20 , 28 30 ]. Galassi et al surveyed a cohort of 175 patients with OMG and compared the outcome of those patients with antibodies to AChR or to MuSK (muscle-specific tyrosine kinase) with those seronegative for both of these antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seropositivity for AChR-Ab as a predictor of generalization is well-documented [ 5 , 7 , 9 11 , 13 , 20 , 28 30 ]. Galassi et al surveyed a cohort of 175 patients with OMG and compared the outcome of those patients with antibodies to AChR or to MuSK (muscle-specific tyrosine kinase) with those seronegative for both of these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have reported risk factors associated with generalization, however, these studies included patients on immunosuppression therapy or those undergoing thymectomy, which may reduce the generalization risk [2,[5][6][7][8][9][10][11][12][13][14]. Thus, a study exploring risk factors in non-immunosuppressed and nonthymectomized patients is required to adequately control for these confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that early immunosuppressive treatment of MG reduces the probability of MC occurrence and recurrence ( 30 ). To date, several retrospective studies showed that the use of oral steroids in ocular MG could reduce the probability of progression to generalized MG ( 31 , 32 ). These results suggest that the use of immunosuppressive therapy in the patients with MG may not only improve symptoms, but also act as a disease modifier to prevent the progression of the disease course in the patients with MG.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, several studies have tried to identify risk factors of secondary generalization to avoid unnecessary adverse effects caused by immunosuppressive medications (9,10,14,15). Thus far, however, it has been challenging to stratify patients with OMG into subgroups with different risk levels of secondary generalization.…”
Section: Discussionmentioning
confidence: 99%